2012
DOI: 10.3390/molecules17066305
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of a-Pinene and β-Pinene Enantiomers

Abstract: The antimicrobial activities of the isomers and enantiomers of pinene were evaluated against bacterial and fungal cells. The agar diffusion test showed that only the positive enantiomers of the α- and β-isomers of pinene were active. The minimal inhibitory concentration (MIC) and minimal microbicidal concentration (MMC) of these monoterpenes were also determined, confirming that the positive enantiomers exhibited microbicidal activity against all fungi and bacteria tested with MICs ranging from 117 to 4,150 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
277
3
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(302 citation statements)
references
References 22 publications
13
277
3
9
Order By: Relevance
“…This result is similar to what was obtained from the leaf essential oil of the plant from Brazil, Iran and Tunisia [30][31][32]. Most of the secondary metabolites present in this essential oil were reported to have good pharmacological properties [33][34][35][36].…”
Section: Chemical Composition Of the Leaf Essential Oilsupporting
confidence: 86%
“…This result is similar to what was obtained from the leaf essential oil of the plant from Brazil, Iran and Tunisia [30][31][32]. Most of the secondary metabolites present in this essential oil were reported to have good pharmacological properties [33][34][35][36].…”
Section: Chemical Composition Of the Leaf Essential Oilsupporting
confidence: 86%
“…Another research developed to evaluate the antimicrobial effects of the different isomers and enantiomers of the monoterpenes as (+) α-pinene and (+) β-Pinene against the gram-negative bacteria species, Proteus vulgaris and C. albicans fungus, where it was possible to verify that Time-Kill curves showed that (+) -α-pinene and (+) -β-pinene were highly toxic to C. albicans, killing 100% of the inoculum in 1 h. In contrast, the bactericidal effect occurred after 6h. In combination with commercial antimicrobials, ciprofloxacin plus (+) -α-pinene or (+) -β-pinene showed synergistic activity against P. vulgaris strain, whereas an indifferent effect against all fungi was detected when amphotericin B was combined with positive pinene enantiomers [12].…”
Section: Resultsmentioning
confidence: 99%
“…32 Candida albicans ATCC 10231 and Aspergillus brasiliensis ATCC 16404 were used in the antifungal assay, since they are responsible for candidiasis and lung infections, respectively. 33 The isolated diterpene showed activity against both MRSA (MIC = 62.5 µg mL -1 ) and C. albicans (MIC = 62.5 µg mL -1 ), and no activity against the Gram-negative bacterium E. coli was observed. It was also inactive against the filamentous fungus A. brasiliensis.…”
Section: Resultsmentioning
confidence: 94%